Wits Architecture Student Works 1922-1980. Wepener, L J. S Ambrogio Milan. Longitudal Section and Plan (first drawings) 1935. BArch III; S Ambrogio, Milan. Facade & Cross Section (second drawings) 1935. BArch III. - Wepener, L J (My University, 2014)
Wits Architecture Student Works 1922-1980. Wepener, L J. S Ambrogio Milan. Longitudal Section and Plan (first drawings) 1935. BArch III; S Ambrogio, Milan. Facade & Cross Section (second drawings) 1935. BArch III.
Wits Architecture Student Works 1922-1980. Wepener, L J. S Ambrogio Milan. Longitudal Section and Plan (first drawings) black ink. 1935. BArch III; S Ambrogio, Milan. Facade & Cross Section (second drawings) black ink. 1935. BArch III.
Keywords: Wits Architecture Student Works 1922-1980. Wepener, L J. S Ambrogio Milan. Longitudal Section and Plan (first drawings) 1935. BArch III; S Ambrogio, Milan. Facade & Cross Section (second drawings) 1935. BArch III.